In-shoe pressure analysis during aero jump in different cadences - Koehler Ribeiro, J.; Fischer, G.; Pivetta Carpes, F.; Bolli Mota, C. (ISB Congress, 2005)
The purpose of this study was to describe the distribution of dynamic pressure during five movements of Aero Jump accomplished in different cadences: 132 bpm (beats per minute) and 145 bpm.